x = (Pi+3)/2
2x = Pi+3
2x(Pi-3) = (Pi+3)(Pi-3)
2Pix-6x = Pi^2-9
9-6x = Pi^2-2Pix
9-6x+x^2 = Pi^2-2Pix+x^2
(3-x)^2 = (Pi-x)^2
3-x = Pi-x
Pi = 3
I have a headache.
i'll take that. Three works for me.
I'm an English major(meaning Math and I are far far apart), so I'll just nod my head and go uhhuh uhhuh. :)
I am not even going to pretend that I grasp that one.
Post a Comment
4 comments:
I have a headache.
i'll take that. Three works for me.
I'm an English major(meaning Math and I are far far apart), so I'll just nod my head and go uhhuh uhhuh. :)
I am not even going to pretend that I grasp that one.
Post a Comment